Arabidopsis XTH4 and XTH9 Contribute to Wood Cell Expansion and Secondary Wall Formation. Issue 4 (31st January 2020) - Kushwah, Sunita; Banasiak, Alicja; Nishikubo, Nobuyuki; Derba-Maceluch, Marta; Majda, Mateusz; Endo, Satoshi; Kumar, Vikash; Gomez, Leonardo; Gorzsas, Andras; McQueen-Mason, Simon; Braam, Janet; Sundberg, Björn; et al.
Abstract : Xylem cell expansion and fiber intrusive tip growth require the activity of enzymes that rearrange xyloglucan in cell walls, and their deficiency not only affects cell expansion but alters subsequent secondary wall formation via cell wall integrity-sensing mechanisms. Abstract: Xyloglucan is the major hemicellulose of dicotyledon primary cell walls, affecting the load-bearing framework with the participation of xyloglucan endo -transglycosylase/hydrolases (XTHs). We used loss- and gain-of function approaches to study functions of XTH4 and XTH9 abundantly expressed in cambial regions during secondary growth of Arabidopsis ( Arabidopsis thaliana ). In secondarily thickened hypocotyls, these enzymes had positive effects on vessel element expansion and fiber intrusive growth. They also stimulated secondary wall thickening but reduced secondary xylem production. Cell wall analyses of inflorescence stems revealed changes in lignin, cellulose, and matrix sugar composition indicating an overall increase in secondary versus primary walls in mutants, indicative of higher xylem production compared with the wild type (since secondary walls were thinner). Intriguingly, the number of secondary cell wall layers compared with the wild type was increased in xth9 and reduced in xth4, whereas the double mutant xth4x9 displayed an intermediate number of layers. These changes correlated with specific Raman signals from the walls, indicating changes in lignin and cellulose. Secondary walls were affected also in the interfascicular fibers, where neither XTH4 nor XTH9 was expressed, indicating that these effects were indirect. Transcripts involved in secondary wall biosynthesis and cell wall integrity sensing, including THESEUS1 and WALL ASSOCIATED KINASE2, were highly induced in the mutants, indicating that deficiency in XTH4 and XTH9 triggers cell wall integrity signaling, which, we propose, stimulates xylem cell production and modulates secondary wall thickening. Prominent effects of XTH4 and XTH9 on secondary xylem support the hypothesis that altered xyloglucan affects wood properties both directly and via cell wall integrity sensing.